Plan de marketing para la empresa de ropa infantil “Baby´s home”, de la ciudad de Quevedo, año 2015 - Villarroel Zamora, Kerly Estefanía (2015)
The implementation of this work is framed in the development of a marketing plan for the company "BABY'S HOME" Quevedo Canton. For the process of quantitative and qualitative research methods were used, which it is applied using techniques of observation, gathering information. The company "BABY'S HOME" has no defined strategies to make yourself known to your target audience and devoid of advertising activities therefore advertising strategies that are made empirically, what little publicity is being done to raise awareness the products and services they offer. In addition the company "BABY'S HOME" does not have a marketing plan, which does not allow a good development in the activities, which affects the process improvement of marketing their products. That is why it is intended to propose a marketing plan that is stated in this document. In the results it was found that the company "BABY'S HOME" does not have the proper advertising, what advertising strategies as the main tool to offer their products and thus significantly increase in sales for the company with the raised meet the demands of its customers, as only in this way you can maintain the position of the company in the market.